PENGGUNAAN FILTRAT RIMPANG JAHE MERAH (Zingiber officinale var. Rubrum) TERHADAP HAMA ULAT BAWANG MERAH (Spodoptera exigua H.) - Riri Dwiyanti; Desita Salbiah (DINAMIKA PERTANIAN, 2022)
Spodoptera exigua H. is a pest on shallot plants. S. exigua pest control is usually performed using synthetic insecticides. However, its use can cause negative impacts on humans and the agricultural environment. Therefor, it needs the alternative insecticides that are safer and environmentally friendly such as Zingiber officinale var. Rubrum. The purpose of this research was to obtain the effective concentration of red ginger rhizome filtrate to control the pest Spodoptera exigua H. The research was conducted at the experimental farm of the Faculty of Agriculture, Riau University from September to November 2019. Experiments were carried out using a completely randomized design (CRD) with 5 treatments and 4 replications. The red ginger rhizome filtrate concentration treatment used was 0 ml.l-1 water, 20 ml.l-1 water, 40 ml.l-1 water, 60 ml.l-1 water, dan 80 ml.l-1 water. The results showed that the concentration of red ginger rhizome filtrate 60 ml.l-1 water could control pests S. exigua and could cause total mortality of 82,50% with an initial death time of 7 hours and lethal time 50 of 40,25 hours.